2013
DOI: 10.1371/journal.pone.0061518
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Immunological Characterization of Ragweed (Ambrosia artemisiifolia L.) Pollen after Exposure of the Plants to Elevated Ozone over a Whole Growing Season

Abstract: Climate change and air pollution, including ozone is known to affect plants and might also influence the ragweed pollen, known to carry strong allergens. We compared the transcriptome of ragweed pollen produced under ambient and elevated ozone by 454-sequencing. An enzyme-linked immunosorbent assay (ELISA) was carried out for the major ragweed allergen Amb a 1. Pollen surface was examined by scanning electron microscopy and attenuated total reflectance–Fourier transform infrared spectroscopy (ATR-FTIR), and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 63 publications
7
69
0
2
Order By: Relevance
“…Studies have demonstrated that pollen concentration is increasing, especially in urban regions (Grewling et al 2012;Ziello et al 2012). Human respiratory systems in urban territories are affected not only by pollen, but also by the components of stationary and mobile air pollution of anthropogenic origin (Puc 2012b;Kanter et al 2013). To maintain quality of life during everyday activities and to ensure timely prevention and diagnosis respiratory disease, it is important to be aware of the spread of pollen.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that pollen concentration is increasing, especially in urban regions (Grewling et al 2012;Ziello et al 2012). Human respiratory systems in urban territories are affected not only by pollen, but also by the components of stationary and mobile air pollution of anthropogenic origin (Puc 2012b;Kanter et al 2013). To maintain quality of life during everyday activities and to ensure timely prevention and diagnosis respiratory disease, it is important to be aware of the spread of pollen.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in individual phenolic metabolites have also been reported in A. artemisiifolia pollen upon CO 2 and/or drought stress [43], whereas no changes were observed upon ozone fumigation [14]. The pollen of several other plants species that were sampled from polluted and less-polluted areas showed an increased amount of individual flavonoids [44] [45].…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…It has been shown that elevated CO 2 concentrations result in an increase of A. artemisiifolia growth and pollen production [9] [10] [11] [12]. In addition to climate change parameters, air pollution might also influence the allergenicity of A. artemisiifolia pollen [13] [14] [15] [16]. However, the fumigation of A. artemisiifolia plants with 80 ppb O 3 did not alter the pollen amount [12].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated ragweed plant exposure to ozone can induce a higher level of expression for Amb a CPI and for the major allergen Amb a 1, as was revealed by transcriptomic assays [80]. …”
Section: Potential New Ragweed Allergensmentioning
confidence: 99%